Models of the ecological hierarchy : from molecules to the ecosphere - Jordan, Ferenc (Oxford : Elsevier, 2012)
In the application of statistics to ecological inference problems, hierarchical models combine explicit models of ecological system structure or dynamics with models of how ecological systems are observed. The principles of hierarchical modeling are applied in this book to a wide range of problems ranging from the molecular level, through populations, ecosystems, landscapes, networks, through to the global ecosphere. Provides an excellent introduction to modelling Collects together in one source a wide range of modelling techniquesCovers a wide range of topics, from the molecular level to the global ecosphere.
Keywords: Ecology; Ecology